2021
DOI: 10.3389/fonc.2021.588136
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Genomic Landscape of Liver Metastasis in Patients With Breast Cancer

Abstract: ObjectiveThe prognosis of breast cancer liver metastasis (BCLM) is poor, and its molecular mechanism is unclear. We aimed to determine the factors that affect the prognosis of patients with BCLM and investigate the genomic landscape of liver metastasis (LM).MethodsWe described the prognosis of patients with BCLM and focused on prognosis prediction for these patients based on clinicopathological factors. Nomogram models were constructed for progression-free survival (PFS) and overall survival (OS) by using a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Recent studies revealed the inhibition of MMP9 which is regulated by α1-ACT, could suppress liver cancer development ( Zhu et al, 2017 ). Previous studies on ESR1 focused on breast cancer, and breast cancer patients highly expressing the ESR1 gene were shown to have a better prognosis; however, recent studies showed that ESR1 is also associated with breast cancer liver metastasis ( De Santo et al, 2019 ; Tian et al, 2021 ). We further found that MMP9 and ESR1 were independent predictors of HCC patient prognosis by performing multifactorial Cox regression analysis and we found that there are strong and significant correlation between MMP9 and ESR1 with CTLA-4.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the inhibition of MMP9 which is regulated by α1-ACT, could suppress liver cancer development ( Zhu et al, 2017 ). Previous studies on ESR1 focused on breast cancer, and breast cancer patients highly expressing the ESR1 gene were shown to have a better prognosis; however, recent studies showed that ESR1 is also associated with breast cancer liver metastasis ( De Santo et al, 2019 ; Tian et al, 2021 ). We further found that MMP9 and ESR1 were independent predictors of HCC patient prognosis by performing multifactorial Cox regression analysis and we found that there are strong and significant correlation between MMP9 and ESR1 with CTLA-4.…”
Section: Discussionmentioning
confidence: 99%
“…Defective DNA mismatch repair further contributes to the progression of liver metastasis. ESR1 has been discovered as the most mutually exclusive mutant gene pair in liver metastasis [96]. ESR1 is an estrogen receptor protein coding gene that is a biological indicator of tumor status in BC.…”
Section: Liver Metastasismentioning
confidence: 99%
“…Focusing on studies that analyzed specific metastases, Tian et al [ 62 ], using the MSKCC Dataset and POTUAM dataset, studied cases of hepatic metastases and unpaired primary breast tumors. They found that the driver genes for liver metastasis (LM) were ESR1 , AKT1 , ERBB2 , and FGFR4 and that LM matched three prominent mutation signatures: APOBEC cytidine deaminase, ultraviolet exposure, and defective DNA mismatch repair.…”
Section: Molecular Landscape Of Bc Metastasismentioning
confidence: 99%